6 alpha-Hydroxy-4[14], 10[15]-guainadien-8 beta, 12-olide induced cell cycle arrest via modulation of EMT and Wnt/beta-catenin pathway in HER-2 positive breast cancer cells - Javir, Gitanjali; Joshi, Kalpana; Khedkar, Vijay; Rojatkar, Supada (Journal of Steroid Biochemistry and Molecular Biology, 2020)
Cyathocline purpurea has potential biological activities and has been widely used in traditional Chinese and Ayurvedic medicine. The aim of the present study is to elucidate the anticancer effect of its 6 alpha-hydroxy-4[14], 10 [15]-guainadien-8 beta, 12-olide (SRCP1) against HER-2 positive subtype of breast carcinoma. Anticancer effect of SRCP1 was assessed by cell viability, senescence, apoptosis, cell cycle, DNA synthesis, and gene expression assays. The activity was further validated by the molecular docking study. SRCP1 inhibits human HER-2 positive breast cancer growth via inhibition of DNA synthesis in a dose-dependent manner. SRCP1 induces cell cycle arrest at G(2)/M phase, late apoptosis, and necrosis. Further, it induces senescence causing reduction in migration via down-regulation of EMT. A remarkable increase in the number of necrotic cells and Annexin-V staining revealed that exposure to SRCP1 triggers late apoptosis. Treatment with SRCP1 increased E-cadherin, p21, p53, ER-alpha expression and decreased beta-catenin, MMP-9, snaill, TNF-alpha expression. SRCP1 showed binding affinity towards an active site of the HER-2 receptor. Our results of molecular docking and biological assays demonstrated the potent anticancer activity of SRCP1 in MDA-MB-453 cells via multiple pathways including EMT, TNF-alpha, and Wnt/beta-catenin signaling.
Keywords: Anticancer; beta-Catenin; EMT; Guaianolide; HER-2 inhibitor